Effect of Mindfulness, Meditation, Yoga on Mental Health - Dr. Kanika Sethi (International Journal of Behavioral Sciences, 2026)
In the last few years to improve quality of life importance has been given to the alternative method of therapy. Yoga, Meditation and Mindfulness has a positive impact on mental well-being. These alternate therapies of healing which help in self-healing tendencies. These alternate ways are both safe and effective treatment and it helps to stimulate positive thinking, destress, resilience, improved interpersonal relationships and increased productivity. Yoga, Meditation and Mindfulness has been offering a holistic approach to health. It helps in offering hope for individuals seeking emotional equilibrium and healing. Yoga itself aims to join the mind and body as well as the individual and universe. According to the study, yoga, meditation, and mindfulness greatly improve people's emotional stability, reduce stress and anxiety, and foster inner calm and spiritual development. This review comprised searches in Medline, Scopus, and Google Scholar and adhered to PRISMA criteria. Due to its emphasis on the mind and body, yoga and mental health are intimately related. As research advances, yoga is emerging as a useful tool for enhancing mental well-being and general well-being in the modern world. Furthermore, regular practice of yoga, meditation, and mindfulness has been associated with improved cognitive functioning, better emotional regulation, and enhanced self-awareness. These practices encourage individuals to develop a balanced perspective toward life challenges, promoting psychological flexibility and adaptive coping mechanisms. By fostering present-moment awareness and reducing negative thought patterns, they contribute significantly to long-term mental wellness, personal growth, and the prevention of stress-related psychological disorders.
Keywords: Self-healing; Therapeutic yoga; emotional stability; mindfulness; spiritual development